Artificial intelligence in action: enhancing reading and writing proficiency in Chinese English learners - Jingdan Liu; Hazrul Abdul Hamid; Xujie Bao (Institute of Advanced Engineering and Science, 2026)
Artificial intelligence (AI) is increasingly adopted in Chinese English as a foreign language (EFL) classrooms, yet its learning benefits remain uncertain in an examination-oriented context where reading and writing proficiency are often constrained. This study employed a quantitative quasi-experimental design with pre- and post-tests, involving 67 non-English-major undergraduates assigned to a control group and an AI-integrated group, to examine AI-supported learning effects on reading and writing within a constructive alignment (CA) framework. Both groups improved after the intervention, while the AI-integrated group demonstrated a notably greater gain in reading performance. The findings suggest that CA can strengthen the effectiveness of AI integration by aligning learning outcomes, activities, and assessment, and that AI use, in turn, can reinforce alignment during the learning process. Pedagogical implications are discussed regarding performance disparity, the extension of CA-guided AI use to other EFL domains, and future instructional research.